Threshold capability development in intensive mode business units. Issue 5 (13th June 2016) - Crispin, Stuart; Hancock, Phil; Male, Sally Amanda; Baillie, Caroline; MacNish, Cara; Leggoe, Jeremy; Ranmuthugala, Dev; Alam, Firoz
Abstract : Purpose: – The purpose of this paper is to explore: student perceptions of threshold concepts and capabilities in postgraduate business education, and the potential impacts of intensive modes of teaching on student understanding of threshold concepts and development of threshold capabilities. Design/methodology/approach: – The student experience of learning was studied in two business units: strategic management, and accounting. The method involved two phases. In the first, students and unit coordinators identified and justified potential threshold concepts and capabilities. In the second, themes were rationalized. Findings: – Significantly more so in intensive mode, the opportunity to ask questions was reported by student participants to support their development of the nominated threshold capabilities. This and other factors reported by students to support their learning in intensive mode are consistent with supporting students to traverse the liminal space within the limited time available in intensive mode. Research limitations/implications: – Respondents from future cohorts will address the small participant numbers. Studies in only two units are reported. Studies in other disciplines are presented elsewhere. Practical implications: – The findings will be important to educators using intensive mode teaching in business, and researchers working within the framework. Originality/value: – This is the first study to explore the potential impacts of intensive modes of teaching on student understanding of threshold concepts and development of threshold capabilities.